Development of New Genetic Algorithm Software for Blow Mould Process - K., Kadirgama; M. M., Noor; R., Daud; M. R. M., Rejab (2008)
This paper is concerned on the optimization of the surface roughness when milling mould aluminium alloys (AA6061-T6) with carbide coated inserts with newly develop Genetic Algorithm (GA) software. Optimization of the milling is very useful to reduce cost and time for machining mould. The approach is based on newly development of Genetic Algorithm software. In this work, the objectives were to optimized parameters with newly develop software and compare with statistical software. The optimized value has been used to develop a blow mould. Results from the newly develop GA software is closer with the statistical software. This software directly reduces in term of machining cost.